Children’s Representations Towards Family Sexual Education Methods: A field study on a sample of children - Keziz, Amel (Social Empowerment Journal, 2024)
This study aimed to try to understand the subject of sex education as it is one of the subjects that may be considered a social taboo that cannot be discussed. Therefore, the focus was on a field study that includes 30 individuals from children, which is a deliberate sample. The questionnaire was distributed to them randomly and represented by children who belong to the late adolescence stage according to the division of scholars and extending from the age of 18 to 21 years, as it is the most conscious of the other stages of adolescence. Through this study, we seek to clarify the dimensions of family upbringing by (parents) and its contribution to forming a sexual culture based on social awareness of such subjects. The descriptive approach was also relied upon as a basic approach to the study, which helped describe the phenomenon scientifically. From here, it was concluded that the family has a set of educational methods that accompany children in such subjects, but they may not be activated to a large extent due to the sum of customs, traditions, and family culture.